Uji Kesukaan Es Krim Kefir Labu Kuning - Amanda Kania Diandini (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2017)
The safe ice cream which is consumed by Diabetes Mellitus sufferers is made by subtituting skim milk, cream and sugar with kefir, pure pumpkin, cornstarch, vegetable oil, and artificial sweetener special gor Diabetes Mellitus. Kefir is known can decrease (blood sugar) because of its bioactive content. The aim of this research is knowing predilection level test to ice cream pumpkin kefir. This research is conducted with experimental method. The data analysis includes predilection test, nutrient value analysis, and price analysis. Ice cream pumpkin kefir that is liked most are from texture side, the cheapest price, and also the highest fiber content exists in balance 578 with the ratio of kefir and pumpkin 50%:50%. Ice cream pumpkin kefir that is liked most from colour side exists in balance 236 with the ratio of kefir and pure pumpkin 70%:30%. Ice cream pumpkin kefir that is liked most from taste side and aroma exists in balance 522 with the ratio between kefir and pure pumpkin 80%:20%.